Influences of work stressors and family support: the mediating role of job performance - Rajpreet Kaur (Vilakshan (XIMB Journal of Management))
Purpose – This present study sheds light on how these issues affect police officers’ personal and professional lives. This research looks at how family support (FS) and workplace pressures affect police effectiveness. Design/methodology/approach – The analysis of the measurement and structural model was conducted using AMOS version 26. To ensure the accuracy of the results, a two-stage analysis methodology (Anderson and Gerbing, 1988) was used. The first stage involved testing the measurement model using various validity indicators such as confirmatory factor analysis, comparative fit index, goodness of fit index and Tucker–Lewis index to evaluate the incremental compatibility of the model. Root-mean-square approximation error and CMIN/DF were also used to further assess the model’s validity. In the second stage of the analysis, the structural model was estimated using structural equation modeling technique (Hair et al., 1998). The data obtained from the measurement model was then used to determine the fit indices. Because the values were consistent with the criterion values, the model was deemed to be a good fit. Findings – The study conducted sheds light on the crucial role that work stressors (WS) and FS play in determining job satisfaction (JS) among nongazetted officers (NGOs) and other ranks (ORs) police officials in the state of Punjab, India. The findings suggest that there exists a complex interdependence between WS and FS, and their correlation with regards to work, family and children’s evaluations. The first hypothesis (H1, Table 4) was found to be true (0.440, p = 0.001), indicating that more than 44 % of the job performance of police officials in Punjab is affected by stressors related to work. The study also identified eight WS that have a significant impact on the performance of police officials on the job. On the other hand, FS was found to have no influence on the job performance of police officials in Punjab, and hence, the second hypothesis was rejected. Further analysis showed that FS was more prevalent among NGOs as compared to ORs police personnel, but it did not directly influence their job performance. The benefits of FS may be moderated by the nature of the job; hence, FS may be more critical in stressful jobs such as police work than in less stressful jobs. The study emphasizes the importance of balancing work and family demands and highlights the need for family-friendly policies to achieve this balance. Future research should focus on the types of policies that should be offered to lessen stress and conflict and examine the benefits of merely offering programs versus requiring or encouraging their usage. The findings of this study could be useful for policymakers and organizations in designing policies that promote employee well-being and JS while balancing work and family demands. Research limitations/implications – As with any research endeavor, it is essential to interpret the findings of this study while considering its limitations. First, the study relied on a convenience sample drawn solely from one nation, namely, India, which may restrict the generalizability of the results to other countries or cultural contexts. Furthermore, it is important to note that this study exclusively explored the causal relationship between monetary compensation, intrinsic motivation and employee performance, without delving into the nuances of various forms or qualities of FS (e.g. emotional support, instrumental support, perceived vs actual support) and their impact on job performance among police officers. Additionally, the research did not investigate whether the influence of FS on job performance varies based on the specific WS encountered by police officers. These limitations highlight potential avenues for future research to explore in greater depth. Practical implications – To enhance the well-being and JS of police officers and their families, a comprehensive set of tailored interventions and support programs can be implemented. Recognizing the unique stressors faced by officers and introducing critical incident debriefing sessions and counseling services to provide a confidential space for emotional processing. Offering flexible scheduling, exploring remote work options and developing workshops and resource programs to address the needs of officers’ families, including stress management and communication skills. Strengthening parental leave policies, incorporating extended paid leave and clear communication, to alleviate stress during significant family events. Establishing peer support networks within police departments to provide officers with a valuable avenue for sharing experiences and coping strategies. Collectively, these interventions aim to create a supportive and family-friendly environment within the police force, ultimately fostering improved work-family balance and enhanced well-being for police personnel. To enhance the well-being and JS of police officers and their families, a comprehensive set of tailored interventions and support programs can be implemented. Recognizing the unique stressors faced by officers, critical incident debriefing sessions and counseling services should be introduced to provide a confidential space for emotional processing. Given the demanding nature of police work, exploring flexible schedules and remote work options can assist officers in achieving a better work-life balance, particularly when dealing with family-related challenges. Workshops and resource programs specifically addressing the needs of officers’ families, including stress management and communication skills, can be developed to strengthen family connections. Strengthening parental leave policies, incorporating extended paid leave and clear communication, can alleviate stress during significant family events. Establishing peer support networks within police departments provides officers with a valuable avenue for sharing experiences and coping strategies. Regular mental health check-ins and screenings, as well as financial education workshops, acknowledge and address the unique challenges faced by officers and their families. Community engagement and recognition initiatives, along with specialized training on work-family balance, can foster positive morale. Finally, the establishment of a crisis intervention and FS hotline serves as a vital lifeline during critical situations, ensuring immediate assistance and resources for officers and their families in times of need. Collectively, these interventions aim to create a supportive and family-friendly environment within the police force. Social implications – The primary objective of this study is to assess the impact of occupational demands and familial support on the overall happiness levels of police officers stationed in Punjab, India. The research underscores the crucial importance of implementing family-friendly policies aimed at achieving a harmonious equilibrium between professional responsibilities and family life commitments. The findings unveil a multifaceted interconnection between occupational stress, familial support systems and individual assessments concerning career fulfillment, domestic life and parental responsibilities. Moreover, the study sheds light on various family-friendly initiatives, such as empowerment strategies and recognition programs, that have the potential to augment JS among police personnel. Furthermore, it suggests that future investigations delve deeper into the efficacy of implementing voluntary programs rather than mandating or promoting their usage in mitigating stress and resolving familial conflicts. The study establishes a clear correlation between JS, overall well-being and the interplay between occupational demands and familial encouragement. Policymakers and corporate entities are urged to take cognizance of these factors while formulating strategies aimed at enhancing the health and contentment levels of employees in the workplace. Additionally, the study underscores the significance of cultural factors, emphasizing the need to consider them in future research endeavors and policy formulations. Cultural factors such as societal norms, values and expectations can influence the way that police personnel perceive and use FS, as well as the impact that FS has on their job performance. By conducting cross-cultural studies, researchers can gain insights into how the relationship between FS and job performance may vary across different cultural contexts. This can help to identify universal factors as well as culturally specific influences on the interplay between FS and job performance among police personnel. Furthermore, investigating the impact of FS on job performance in diverse cultural contexts can contribute to the development of culturally sensitive support programs and policies for police officers. Understanding how cultural factors shape the experiences of police personnel and their families can inform the design of interventions that are tailored to the specific needs and challenges present in different cultural settings. In summary, expanding the research scope to include diverse cultural contexts can enhance the generalizability of the findings and contribute to the development of culturally sensitive support programs and policies for police officers. Originality/value – The content of this paper is entirely original and has not been derived from any other published or unpublished documents. It has been created solely for the purpose of providing new and unique information for the readers.